2003
DOI: 10.1007/s00701-003-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations: influence of angioarchitecture on bleeding risk

Abstract: Various angiographic features were correlated with the occurrence of intracranial haemorrhage in patients with cerebral AVMs. In addition to the well-known factors influencing the bleeding risk of cAVMs like size, pattern of venous drainage and location within the brain our data demonstrate the importance to look at the diameter of the main feeder and the number of draining veins showing a better correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
1
11
1
3
Order By: Relevance
“…Some studies report increased risk of hemorrhage, 4, 9, 18, 20, 23, 24 while other reports suggest no independent effect. 11, 12, 25 Venous stenosis offered no predictive value in the current study. Of course, cerebral veins that are completely thrombosed are not directly visible on DSA and only inconsistently identifiable on CT and MRI, thus limiting the utility of this measure.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Some studies report increased risk of hemorrhage, 4, 9, 18, 20, 23, 24 while other reports suggest no independent effect. 11, 12, 25 Venous stenosis offered no predictive value in the current study. Of course, cerebral veins that are completely thrombosed are not directly visible on DSA and only inconsistently identifiable on CT and MRI, thus limiting the utility of this measure.…”
Section: Discussioncontrasting
confidence: 74%
“…Some studies report increased risk of hemorrhage, 8, 13, 18, 19 while other reports suggest no impact 12 or a protective role for ectasia. 11, 20 This study found that venous ectasia is inversely related to intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Annual ICH rates in untreated AVMs range from about 2 to 4% . These rates may vary according to several AVM characteristics, such as location, venous drainage, lesion size, presence of associated aneurysms, or history of previous bleeding . It has long been hypothesized that unruptured and untreated high‐grade AVMs may have a higher risk of subsequent bleeding than those of low‐grade lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other factors that are important for the evaluation of AVMs or deemed as significant determinants of risks and outcomes such as the pattern of supplying artery and draining vein, AVM related aneurysms, presence of arteriovenous fistula (AVF) and detailed hemodynamic information were evaluated 8–10 . These results were then compared with those of DSA and TOF MRA respectively to test whether the information derived from dynamic MRA is consistent with the gold standard of DSA, and whether dynamic MRA will improve the existing diagnosis based on TOF MRA.…”
Section: Introductionmentioning
confidence: 99%